Explaining burnout and the intention to leave the profession among health professionals – a cross-sectional study in a hospital setting in Switzerland - Oliver Hämmig (BMC Health Services Research, 2018)
Abstract Background Burnout and the intention to leave the profession are frequently studied outcomes in healthcare settings that have not been investigated together and across different health professions before. This study aimed to examine work-related explanatory factors or predictors of burnout and the intention to leave the profession among health professionals in general, and nurses and physicians in particular. Methods Cross-sectional survey data of 1840 employees of six public hospitals and rehabilitation clinics recorded in 2015/16 in German-speaking Switzerland were used. Multiple logistic and stepwise linear regression analyses were performed to estimate the relative risks (odds ratios) and standardized effects (beta coefficients) of different workloads and work-related stressors on these outcomes and to study any possible mediation between them. Results On average, one in twelve health professionals showed increased burnout symptoms and every sixth one thought frequently of leaving the profession. Temporal, physical, emotional and mental workloads and job stresses were strongly and positively associated with burnout symptoms and thoughts of leaving the profession. However, the relative risks of increased burnout symptoms and frequent thoughts of leaving the profession were highest in the case of effort-reward and work-life imbalances. In fact, these two work-related stress measures partly or even largely mediated the relationships between exposures (workloads, job stresses) and outcomes and were found to be the strongest predictors of all. Whereas a work-life imbalance most strongly predicted burnout symptoms among health professionals (β = .35), and particularly physicians (β = .48), an effort-reward imbalance most strongly predicted thoughts of leaving the profession (β = .31–36). A substantial part of the variance was explained in the fully specified regression models across both major health professions and both outcomes. However, explained variance was most pronounced for burnout symptoms of physicians (43.3%) and for frequent thoughts of leaving the profession among nurses and midwives (28.7%). Conclusions Reducing workload and job stress, and particularly reward frustration at work, as well as the difficulties in combining work and private lives among health professionals, may help to prevent them from developing burnout and/or leaving the profession and consequently also to reduce turnover, early retirement, career endings and understaffing in healthcare settings.